GENOTOXIC EFFECTS OF AQUATIC EXTRACT OF ENDEMIC PLANT ONOSMA STELLULATA WALDST. & KIT. (BORAGINACEAE) - Redzic, A.; Redzic, S.; Sejdic, N. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
The species of genus Onosma contain pyrrolizidine alkaloids [1] and use in treatment of lung cancer and other respiratory diseases in some regions of W. Balkan [2, 3] .Goal of this study is to research genotoxic effects of over ground and underground parts of species Onosma stellulata in vitro conditions. Floral material for this research was collected during May and June of 2006 in area of Herzegovina (W. Balkan). Floral samples were dried and exposed to double mazzeration in accordance with Ph.Yug. IV in order to receive extract that was used in making 0.05% and 0.10% solution. Evaluation of geno-toxic effect was conducted by using Allium-test, along with observation of chromosomes abnormalities (partition spindle, irregular phases, multi-polarity, stagnating chromosomes, C-mitosis, and others). Effects were observed after 4, 8, 12 and 24-hours treatments. Testing of differences between determined (experimental group) and expected (control group) was conducted by using X2 test. Extracts of both concentrations, both over and under ground parts and root, are causing geno-toxic effects in mitosis at meristematic cells of onion. Genotoxic effect is in co-relation with length of treatment and solution concentration. Aquatic extract of over ground part showed distinguished geno-toxic effect after 4-hours treatment (mitotic index was 2, 79%, and in control was 9, 18%). Determined was also statistically significant difference for 0, 10% extract of over ground part (p≤0.05). Higher degree of geno-toxic effect was determined for root extract. Genotoxic effect is reflected at changes in structure of chromosomes (conglutination, spirality), and cito-toxic reaction and certain variations in cell cycle.References:1. El-Shazly A et al. (2003). Biochemical Systematics and Ecology, 31( 5): 477-485. 2. Redzic SS (2007) Coll. Antropol. 31: 869-890 3. Redzic S (2007) Planta Med. 73: 1013.